145 Determination of the Optimal Stage of Lactation for Infectious Bovine Keratoconjunctivitis Vaccination. (1st March 2018) - Dhom, A R; Flatow, L A; Griffin, M E; Gribble, W M; Stucky, J C
Abstract: At the onset of lactation, dairy cattle are at risk for developing diseases resulting from the reallocation of resources toward maintaining lactation and away from the immune system. This can lead to less powerful immune responses and increased incidences of infection. In order to continue to maintain herd health, yearly vaccinations need to be administered during the lactation period, but they may not be effective if the immune system is suppressed. The purpose of this study was to determine an ideal stage of lactation in which to administer vaccinations against infectious bovine keratoconjunctivitis. Twenty-four lactating Jersey cows were divided into 3 groups based on phase of lactation: early lactation (14–100 days in milk), mid lactation (101–200 days in milk), and late lactation (201–305 days in milk). On day 0, On day 0, serum and lacrimal secretion samples were collected, and cows were vaccinated intramuscularly against Moraxella bovis . Serum and lacrimal secretion samples were collected again on days 7 and 14. Serum IgG concentrations and lacrimal IgA concentrations against M. bovis were measured by ELISA. Data was analyzed using one-way repeated measures ANOVA with stage of lactation as the main effect. While vaccination did result in an increase in antibody concentrations against M. bovis by day 14 post-vaccination, phase of lactation had no effect on serum IgG (P=0.189) or lacrimal IgA (P=0.520) concentrations. This data indicates that the phase of lactation may not need to be taken into consideration when designing a vaccination schedule for dairy cows. Future studies using a larger sample size are warranted.